Cognitive behaviors in Indonesian-English translation: Exploring translation processes - Andi Rustandi (Universitas Galuh, 2023)
This present study investigated the cognitive behaviors in the processes of Indonesian-English translation. Two research questions were employed to find out; 1) what types of cognitive behaviors emerge in the translation processes, 2) and which types of cognitive behavior are the most dominant in the translation process? The data were taken from screen recording of translator activities in video supplemented by think-aloud protocols in TransCon6_ID.mp4 entitled